Sistem Informasi Helpdesk TicketingDinas Komunikasi, Informatika, Statistik dan Persandian Kabupaten Banjar Berbasis Website - Agung Wibobo, Dwi; Syafaadi Rizki, Afian; Noor Abdul Muhid, Andrean (mijournal.org, 2024)
The Department of Communication, Informatics, Statistics, and Cryptography of Banjar Regency faces operational inefficiencies due to service disruptions. To address this issue, a Web-Based Helpdesk Ticketing Information System was designed and developed using the CodeIgniter 3 framework, PHP, Bootstrap, and MySQL. This system facilitates efficient, accurate, and documented IT complaint management, with users consisting of Admin, Technicians, and Reporting Users. The implementation results indicate that the system enhances efficiency, transparency, and service performance, supporting the optimization of technology within government institutions.